The Influence Of The Work Environment On Employee Work Comfort (Case Study: Regional Disaster Management Agency, Pematangsiantar City) - Lia Agatha Hutajulu; Jufri Antoni (LPPM Universitas PGRI Sumatera Barat, 2024)
The Influence of the Work Environment on Employee Work Comfort. The case study at the Regional Disaster Management Agency Office was formed because various disasters that were motivated by geographical, geological, hydrological and demographic conditions encouraged Indonesia to build a vision to build the nation's resilience in facing disasters. The purpose of this research is to determine the influencing factors of the work environment on employee comfort. The population in this study were all employees of the Pematangsiantar Regional Disaster Management Agency office, methods or techniques for collecting data in this study used questionnaires, interviews. The results of this research indicate that a good or positive relationship (correlation) was obtained between environmental variables and the level of work comfort of employees at the Pematangsiantar Regional Disaster Management Agency office